Appropriation under Low Intellectual Property Regimes: The Role of Communities in the Online Alternative Adult Entertainment Industry - LE, Kim-Marlène; PÉNIN, Julien (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2017)
The online adult entertainment industry, as Darling (2014) showed, is a new case of low intellectual property regime, i.e. largely inefficient in preventing the massive copying of content. In this paper, we focus on alternative pornography and explore the mechanisms which contribute to the creation of pornographic content. We argue that user communities help content providers to absorb sunk costs associated with content production and distribution. Our main conclusion is that, although user communities cannot solve alone the incentive failure in online pornography, they complement and reinforce strategies which enable content producers to earn revenues from vulnerable copyrighted works.